Circumventing the Nation: How to Develop a Postcolonial Archive on Public Health in India - Aprajita Sarcar (Revue Internationale des Études du Développement)
Historiography on late colonial public health governance in India has detailed the imprints of transnational funders, namely the Rockfeller Foundation and later, the Ford foundation on funding, research, and knowledge production around national programmes and personnel in India. The National Archives in India, is significantly thin on subjects like demography, reproductive policies and birth control technologies. Scholars have to necessarily rely on transnational repositories. This paper will analyze some of the ethical dilemmas of using these transnational sources. I suggest we seek municipal counterparts and decenter the nation. Juxtaposing the transnational with the local archival trail opens up new conversations about networks that emerged within overlapping funding priorities.